The Mill River redemption [large type] : a novel - Chan, Darcie (Thorndike Press, 2014)
"Having unexpectedly lost her husband and lacking the means to support herself and her two young daughters, Josie DiSanti takes refuge with her aunt in Mill River, Vermont. Thanks to Aunt Ivy, who runs the town's book shop, the community quickly come to know Josie and her girls, Rose and Emily. The sisters are inseparable growing up, but in their early college years, a tragedy tears them apart. Years later, the sisters agree to return for the reading of their mother's will, where they learn that Josie has devised a last-ditch attempt to force their reconciliation. They must move into neighboring houses for the summer and cooperate to locate the key to Josie's safe deposit box. Rose and Emily have no choice but to go along with their mother's scheme and try to find it within themselves to learn to become sisters again"--